Beginning Scala 3: A Functional and Object-Oriented Java Language, 3rd Edition - Pollak, David; Layka, Vishal; Sacco, Andres (Apress, 2022)
This book introduces you to the Scala programming language, its object-oriented and functional programming characteristics, and then guides you through Scala constructs and libraries that allow you to assemble small components into high-performance, scalable systems. --